Frontal alpha asymmetry interaction with an experimental story EEG brain-computer interface - Krogmeier, Claudia; Coventry, Brandon S.; Mousas, Christos (Frontiers in Human Neuroscience, 2022)
Although interest in brain-computer interfaces (BCI) from researchers and consumers continues to increase, many BCIs lack the complexity and imaginative properties thought to guide users towards successful brain activity modulation. We investigate the possibility of using a complex BCI by developing an avant-garde story environment with which users interact through imagination-based cognitive thought strategies. In our system, the user's frontal alpha asymmetry (FAA) measured with electroencephalography (EEG) is linearly mapped to the color saturation of the main character in the story. We implemented a user-friendly experimental design using a comfortable EEG device and short neurofeedback (NF) training protocol. In our system, several participants successfully increased FAA during the course of the study. We detail our results concerning left and right prefrontal cortical activity contributions to FAA in both successful and unsuccessful story blocks. Additionally, we examine inter-subject correlations of EEG data, and self-reported questionnaire data to understand the user experience of BCI interaction. Results suggest the potential of imaginative story BCI environments for engaging users and allowing for FAA modulation. Our data suggests new research directions for BCIs investigating emotion and motivation through FAA.